Severe osteonecrosis of the jaws in a compromised patient subjected to bisphosphonate therapy - Juliana Dreyer de Menezes; Nicole de Mello Rahde; Fernanda Gonçalves Salum; Maria Antonia Figueiredo; Karen Cherubini
Bisphosphonate-related osteonecrosis of the jaws is characterized by alveolar bone exposure, especially after mucosal trauma or after surgical procedures, in patients who have previously received or who are currently receiving bisphosphonates without a history of radiation therapy in the maxillofacial region. The condition is refractory to treatment, and attempts at debridement are not completely effective in eradicating the necrotic bone. We report here a case of a severe osteonecrosis of the jaws in a 77-year-old male patient, who had been subjected to chemotherapy and treatment with zoledronic acid and corticosteroid. The patient also had comorbidities such as diabetes and periodontal disease, which might have contributed to the lesion development. Bisphosphonate-related osteonecrosis of the jaws has become a reality in dental clinical practice. Although palliative treatment aiming at controlling pain, infection and injury progression is indicated, the therapeutic strategy is still challenging. So far, the best approach available is prevention, based on oral care before, during, and after bisphosphonate therapy.